2017
DOI: 10.1016/j.yfrne.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary consensus on the therapeutic recommendations for iatrogenic hyperprolactinemia secondary to antipsychotics

Abstract: Hyperprolactinemia is an underappreciated/unknown adverse effects of antipsychotics. The consequences of hyperprolactinemia compromise therapeutic adherence and can be serious. We present the consensus recommendations made by a group of experts regarding the management of antipsychotic-induced hyperprolactinemia. The current consensus was developed in 3 phases: 1, review of the scientific literature; 2, subsequent round table discussion to attempt to reach a consensus among the experts; and 3, review by all of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 120 publications
(90 reference statements)
1
40
0
4
Order By: Relevance
“…Hence, antipsychotics with a greater D2 occupation index produce significant prolactin elevation 21 . Our previous study revealed that prolactin levels significantly increase after administering a single dose of OLA 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, antipsychotics with a greater D2 occupation index produce significant prolactin elevation 21 . Our previous study revealed that prolactin levels significantly increase after administering a single dose of OLA 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Risperidone, amisulpride and paliperidone are more likely than other compounds to cause it 842. Hyperprolactinaemia can induce amenorrhoea, sexual dysfunction, and galactorrhoea, amongst other effects.…”
Section: Safety and Monitoringmentioning
confidence: 99%
“…The Spanish consensus on the risks and detection of antipsychotic drug-related hyperprolactinemia suggests that prolactin levels over 50 ng/ml or with clinical symptoms require the adaptation of antipsychotic medication (lowering doses, changing the antipsychotic, adding substances known to decrease prolactin levels such as aripiprazole). In case of severe hyperprolactinemia (over 100 ng/ml) the intervention is always recommended, even in the absence of clinical symptomatology, because of the medium and long-term risk of osteoporosis, cardiovascular complications and possible increase in breast or endometrial cancer [12,13].…”
Section: Introductionmentioning
confidence: 99%